The Influence of Servant Leadership on Innovative Work Behavior in the Banking Services Sector: The Role of Work Engagement and Perceived Organizational Support - Hayati, Ni Wayan; Purwanto, Purwanto (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2026)
The dynamic and competitive business environment requires the banking sector to continuously improve efficiency, service quality, and responsiveness to customer needs. In this highly regulated, compliance-driven context, employees’ innovative work behavior (IWB) plays a critical role in sustaining organizational competitiveness and service excellence. This study examines the direct effects of servant leadership on innovative work behavior in the banking sector, while also considering the roles of perceived organizational support (POS) and work engagement as explanatory variables. A quantitative research approach was employed, with data collected through an online survey conducted in April 2025 involving 181 permanent and contract employees at staff and officer levels in the Indonesian banking sector. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that servant leadership has a positive and significant effect on both work engagement and perceived organizational support. Work engagement, in turn, shows a positive and significant effect on innovative work behavior. However, the direct effects of POS on work engagement and servant leadership on IWB, although positive, are not statistically significant. The results indicate that servant leadership has a positive and significant effect on both work engagement and perceived organizational support. Work engagement, in turn, shows a positive and significant effect on innovative work behavior. However, the direct effects of perceived organizational support on work engagement and servant leadership on innovative work behavior, although positive, are not statistically significant.